E-Dakwah Melalui Media Virtual Di tengah Social Distance - Ila Khafia Wafda (Multimatrix, 2020)
E-Da’wah is alternative propaganda through internet media to facilitate its users. E-Dakwah makes it easy for its users to find out about Islam as well as expand its reach for da’wah. This phenomenon is integrated because it is line with the times. This E-Da’wah activity was initiated by several communities, one of which was a community in Islamic studies that was active in da’wah through virtual media. In addition, Indonesia is one of the countries affected by the Corona-19 outbreak which requires people to maintain social distance by staying at home and doing activities at home. With the regulation of social distance from the goverment, preachers and the public do not attend recitals, which are ussually held routinely. But virtual media has made it easy for preachers to be able to broadcast Islamic knowledge through several virtual media, for example through the web, Youtube and social media. Preachers can easily create e-mails and then accounts, the they can easily make propaganda messages. Broadcast short videos titled Islamic, updated Islamic material can be accessed through blogs or websites  from preachers as well as through social media accounts from propaganda activists.  Keywords: E-Da’wah, virtual media dan social distancing